2014
DOI: 10.1016/s2214-109x(14)70224-4
|View full text |Cite
|
Sign up to set email alerts
|

Population effect of 10-valent pneumococcal conjugate vaccine on nasopharyngeal carriage of Streptococcus pneumoniae and non-typeable Haemophilus influenzae in Kilifi, Kenya: findings from cross-sectional carriage studies

Abstract: SummaryBackgroundThe effect of 7-valent pneumococcal conjugate vaccine (PCV) in developed countries was enhanced by indirect protection of unvaccinated individuals, mediated by reduced nasopharyngeal carriage of vaccine-serotype pneumococci. The potential indirect protection of 10-valent PCV (PCV10) in a developing country setting is unknown. We sought to estimate the effectiveness of introduction of PCV10 in Kenya against carriage of vaccine serotypes and its effect on other bacteria.MethodsPCV10 was introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
161
8
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(192 citation statements)
references
References 46 publications
22
161
8
1
Order By: Relevance
“…30 Conjugate vaccine serotypes causing IPD were highly prevalent (> 60% of serotypes) in 2 studies. 6,57 Prevalence of serotypes uniquely covered by PPV23 was reported in 4 studies 6,9,24,57 2 of which reported 12F to be most prevalent.…”
Section: Pneumococcal Serotype Distribution Among Adults Aged 15-59 Ymentioning
confidence: 99%
“…30 Conjugate vaccine serotypes causing IPD were highly prevalent (> 60% of serotypes) in 2 studies. 6,57 Prevalence of serotypes uniquely covered by PPV23 was reported in 4 studies 6,9,24,57 2 of which reported 12F to be most prevalent.…”
Section: Pneumococcal Serotype Distribution Among Adults Aged 15-59 Ymentioning
confidence: 99%
“…Tenvalent PCV (PCV10) and PCV13, specially recommended for children younger than 2 years of age, induce a high antibody response against included serotypes, protect against invasive diseases, and reduce pneumococcal carriage (4,5). One of the main limitations of these serotype-specific vaccines is the "serotype replacement" effect.…”
mentioning
confidence: 99%
“…First, vaccinations are commonly given in early life phases, and the returns on vaccination investments, such as improved school attainment, economic productivity, and social functioning, are reaped throughout the life course (31)(32)(33). Second, vaccinations often disrupt transmission chains of infectious diseases throughout the community, leading to multiplier effects for the broader economic and social benefits of vaccination (20,(39)(40)(41)(42)(43)(44)67). Third, the child survival benefits of vaccinations typically catalyze or accelerate fertility decline and create potentially sizable opportunities for economic growth.…”
Section: Discussionmentioning
confidence: 99%
“…Community health externalities include herd effects, whereby unvaccinated members of a community incur protection from disease through the vaccination of others (39)(40)(41)(42)(43)(44)(45)(46)(47). They also include reduced use of antibiotics to fight vaccine-preventable diseases and, as a consequence, slower development of antibiotic resistance (48,49).…”
Section: Broader Perspective On the Value Of Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation